The Infleunce of Customer Experience, Customer Satisfaction & Customer Loyalty Towards Brand Power (Study on Go-Ride Service by Gojek in Bandar Lampung) - Syauqi, Muhammad Ryan; Pandjaitan, Dorothy Rouly Haratua; Nabila, Nuzul Inas (PT FORMOSA CENDEKIA GLOBAL, 2023)
Amid intensifying competition within the ride-hailing sector, characterized by increased tightness and difficulty, maintaining a long-term competitive edge becomes crucial for a company's survival. Numerous scholars and industry professionals advocate that achieving competitive advantage as a firm entails prioritizing customer-centric strategies aimed at surpassing competitors through superior and expedited fulfillment of client wants. This study examines the impact of customer experience, customer satisfaction, and loyalty on the brand power of the Go-Ride service provided by Gojek. The study questionnaire was administered to a sample population consisting of 177 clients of Gojek, from whose data was collected. This inquiry pertains to using questionnaires as a means of data gathering, specifically focusing on those procedures that have undergone rigorous testing to establish their validity and reliability. The study's findings indicate that customer experience shapes customer satisfaction. Moreover, customer satisfaction has a favorable impact on brand power. Additionally, customer satisfaction influences customer loyalty, affecting brand power. However, the statistical findings did not provide evidence to support the notion that customer experience has a beneficial impact on brand power and customer loyalty